EXPLORING THE HUMANISM PHILOSOPHY THROUGH MOBILE LEARNING IN INDONESIA - Alfitriani Siregar; Idris Eal Al Amini (Academic Solution Publisher, 2026)
This study aimed to explore the fuctions of humanism philosophy in mobile learning (m-learning) in Indonesia. Using a qualitative approach through library research, this study analyzed the literature related to humanistic philosophy, educational technology, national regulations, and empirical studies on m-learning. The findings included (1) the shift in the teacher’s role toward a digital facilitator, (2) students’ self-actualization and learning autonomy in m-learning, (3) the integration of human values in the digital era and the challenges of social interaction, and (4) the alignment between educational regulations and philosophical foundations. Mobile learning has proven to support flexibility and independent learning; however, its predominantly technocentric use potentially weakens human values such as empathy, dialogue, and emotional closeness. Although national educational regulations through Merdeka Belajar policy are aligned with the humanistic approach, the implementation of m-learning requires more concrete pedagogical guidelines to ensure that technology truly humanizes learners. This study concluded that the integration of humanistic philosophy is essential in transforming m-learning from merely a medium for information delivery into a platform for self-development, character building, and the preservation of students’ dignity.